Education for parents regarding choking prevention and handling on children: a scoping review - Marlyn Anggelina Pondete; Wisnu Barlianto; Suryanto Suryanto (International Journal of Public Health Science (IJPHS), 2022)
Choking is a pediatric emergency that threatens life. Choking occurs in 80% of under three-year-old children worldwide. Many children do not receive help since the aid provider fears causing harm due to the absence of choking case knowledge. Improving parent’s knowledge can decrease choking risk in children that threatens life. This scoping review aimed to identify education provision regarding foreign body aspiration on children. This study was a scoping review with choking handling articles to identify education provisions regarding choking handling on children. Article search was carried out using internet databases, i.e., PubMed, Proquest, and Sciencedirect. The selection was performed using a PRISMA flow diagram. The search results obtained 1,081 literatures, title-screening excluded 948 articles and obtaining 98 articles to be tested for eligibility. The 91 articles with unrelated objectives were excluded. Seven remaining articles following the inclusion criteria were identified. Providing education for parents about choking prevention and handling on children is an essential component of the public health approach as video-based e-learning program, direct learning, installation of hazard warning of choking. Educational programs will be effective when utilizing various information sources and assigning additional healthcare providers tasks to educate parents and the community.